Book review: The “war on gender” as protest against the international order - José Antonio Sanahuja (Revista CIDOB d'Afers Internacionals)
Review of the book: Barbé, Esther y Martín, Magdalena M. (dirs.). La violencia contra las mujeres en un orden internacional en transición. Aranzadi, 2024, 379 págs.